Small extracellular vesicles in metabolic remodeling of tumor cells: Cargos and translational application - Yang, Hao; Wang, Jingyi; Huang, Gang (Frontiers in Pharmacology, 2022)
Warburg effect is characterized by excessive consumption of glucose by the tumor cells under both aerobic and hypoxic conditions. This metabolic reprogramming allows the tumor cells to adapt to the unique microenvironment and proliferate rapidly, and also promotes tumor metastasis and therapy resistance. Metabolic reprogramming of tumor cells is driven by the aberrant expression and activity of metabolic enzymes, which results in the accumulation of oncometabolites, and the hyperactivation of intracellular growth signals. Recent studies suggest that tumor-associated metabolic remodeling also depends on intercellular communication within the tumor microenvironment (TME). Small extracellular vesicles (sEVs), also known as exosomes, are smaller than 200 nm in diameter and are formed by the fusion of multivesicular bodies with the plasma membrane. The sEVs are instrumental in transporting cargoes such as proteins, nucleic acids or metabolites between the tumor, stromal and immune cells of the TME, and are thus involved in reprogramming the glucose metabolism of recipient cells. In this review, we have summarized the biogenesis and functions of sEVs and metabolic cargos, and the mechanisms through they drive the Warburg effect. Furthermore, the potential applications of targeting sEV-mediated metabolic pathways in tumor liquid biopsy, imaging diagnosis and drug development have also been discussed.